Felis catus as a model to study follicle biology in vitro - Rojo, Julieta Laura (2015)
Purpose The current study was designed to evaluate the responseof individual intact antral follicles from adult femaledomestic cats to a luteinizing hormone (LH) stimulus in vitroby assessing cumulus-oocyte expansion (C-OE) and steroidproduction.Methods C-OE and steroid levels (estradiol [E2] and progesterone[P4]) obtained from individual antral feline follicles(n=366 follicles; n=56 cats) were analyzed after 12 or 24 hof culture in the presence or absence of LH (low [3.4 ng/ml] orhigh [100 ng/ml]).Results At the end of the culture, the highest percentage ofexpanded cumulus-oocyte complexes (COCs) was observedin the LH groups at 12 or 24 h in comparison to their controls(p<0.001). There was a significant increase in expandedCOCs when comparing LH concentrations (high vs. low) at12 or 24 h. Higher levels of both E2 and P4 were observed inthe media from antral follicles after 12 and 24 h of culture inthe presence of LH (both concentration, p<0.05). There wasno association between hormone levels and follicle diameter;high variability was observed in the steroid levels produced byantral follicles within all treatment groups.Conclusions These data indicate, for the first time, that felineantral follicles (0.5-2 mm) from different stages of the naturalestrous cycle can be cultured and will respond to an LH stimulus,based on an increase in steroid levels as well as C-OEafter 12 or 24 h in culture.